Sanitary landfill leachate treatment by physico-chemical and biological methods: a comparative study / Norhayati Mohd Idrus - Mohd Idrus, Norhayati (2008)
Landfill is one of the most widely employed methods for the disposal of municipal solid waste (MSW). Up to 95% of total MSW collected worldwide is disposed of in landfills. After landfilling, solid waste undergoes physico-chemical and biological changes. Consequently, the degradation of the organic fraction of the wastes in combination with percolating rainwater leads to the generation of leachate. If not properly treated, leachate that seeps from a landfill can enter the underlying groundwater, thus posing potentially serious hazards to the surrounding environment and to public health. As a result, the search for effective and efficient treatment technologies landfill leachate has intensified in recent years. In this study, the applicability and treatment performance of physicochemical methods and biological method (as either individual and/or combined) for landfill leachate are reviewed. The study on coagulation-flocculation and Fenton's reagent method as physico-chemical treatment process, while activated sludge and biofilter were used as biological treatment methods. The advantages and limitations of various techniques are evaluated. Their operating conditions such as pH, coagulant and coagulant aid dosage, characteristics of leachate in terms of COD, NH3-N, total-nitrogen and color concentration and treatment efficiency are compared. The results obtained indicate that individual physico-chemical treatment is less effective than the integrated treatment. It is found that Fenton’s reagent could remove highest, of COD, NH3-N, total-nitrogen and color from landfill leachate, namely 89%, 95%, 86% and 81%, respectively, when compared to coagulation and flocculation process. A combination of physico-chemical and biological treatment has demonstrated high efficiency for the treatment of stabilized leachate. Almost complete removal of COD, NH3-N, totalnitrogen and color from landfill leachate, has been accomplished by a combination of Fenton’s reagent and a biofilter, namely 93.5%, 97.7%, 98.0% and 99.2%, respectively.